South African historians and continental contact (Historia, 2021)
Since the nineties of the twentieth century especially Afrikaans speaking South African historians experiences an exceptional l process of consciousness. For the first time in more than three decades was it possible to establish contact with subject colleagues in all parts of the world.The era of political, economic and social isolation left its mark. It was and is still difficult to move beyond an archaic appraisal of cherished intellectual bonds with the European continent. There are promising signs that we are making progress. The process has however not yet reached a level of innovative synthesis. It is anticipated this will soon follow. In this edition of Historia there are two contributions of leading European philosophers of history. Proff. Jőrn Rűsen of Germany, and Frank Ankersmit of the Netherlands visited South Africa earlier this year and held discussions with their South African counterparts at various universities. They also addressed the biennial conference of the Historical Association of South Africa in August.
Keywords: consciousness; political; economic and social; intellectual bonds; Historia